Artificial intelligence in sports: potentialities and implementation ways and tools - Morkhat, P. M. (Theory and Practice of Physical Culture, 2018)
The study analyzes the legal and technical basics, means and potentialities for the modern artificial intelligence technology implementation in sports, including elements of artificial intelligence applicable in the sport refereeing service in competitions to ensure fair and unbiased service; in the points scoring; in detection of violations; in the government management of the sports sector, including the risk assessment and contingency planning components; in the individual/ team coaching service; in the sport event broadcasting service; in the competitive result forecasts; in the sport science on the whole and sport biomechanics in particular; in the new training system design; in the sport equipment and accessories design and production processes; in the sport garments and footwear designs; in the anti-doping service etc. The study analyzes in detail the pros and cons of the initiatives to apply artificial intelligence technologies and units in modern sports. It was found that at this juncture and in the nearest future the existing artificial intelligence technologies will unlikely fully replace the traditional sport referees by some artificial intelligence-technology-based electronic applications. However, artificial intelligence technology applications in sports are quite promising, particularly in logistical, processing and potentially corruptive operations in the sport management system.